Effect of withdrawing long-term CPAP therapy on the course of obstructive sleep apnea - M. V. Agaltsov; O. M. Drapkina (Российский кардиологический журнал, 2021)
Aim. To assess the effect of withdrawing long-term (12 months) CPAP therapy on the course of obstructive sleep apnea (OSA) in patients with moderate to severe disease.Material and methods. The study included 40 patients with moderate to severe OSA and paroxysmal atrial fibrillation (AF) after surgical treatment. The mean age of the subjects was 59,3+8,2 years. In addition, 55% of patients had obesity. All patients were started on CPAP therapy. After 12 months, CPAP therapy was canceled in the patients who completed the study. Additional cardiorespiratory sleep monitoring was performed 1-2 days after the withdrawal of treatment to assess the severity of sleep-related breathing disorders.Results. Cancellation of CPAP therapy in all observed cases led to an immediate relapse of OSA. Although the mean value of the apnea/hypopnea index (AHI) decreased from 24 episodes per hour [20; 34] before treatment up to 21 episodes per hour [13; 27] after 12-month CPAP therapy, there was no significant difference before and after therapy. In addition, the statistical analysis showed a transition from more severe OSA degrees to moderate ones, depending on the initial severity of the disease. Correlation analysis demonstrated significant relationships of the OSA severity, the final AHI value and the minimum oxygen level with the patient’s body weight (before and after therapy) (r=0,396, 0,411 and -0,488; r=0,358, 0,398 and -0,44, respectively, p<0,05).Conclusion. In our study, when the 12-month CPAP therapy was canceled, no complete cure for sleep-related breathing disorders was recorded in any case. OSA recurrence was recorded immediately after discontinuation of CPAP therapy (on days 1-2) and its severity depended on the initial severity of the disease. At present, the continuation of CPAP therapy remains the only way to achieve complete control of OSA as a risk factor for AF.